Targeting the UCP1-dependent thermogenesis pathway with CRISPR/Cas9: a new approach to obesity management - Esmail Karami; Fatemeh Rostamkhani; Maasoume Abdollahi; Mohamadreza Ahmadifard (Current Research in Biotechnology)
Obesity is a complex, multifactorial disease characterized by excessive body fat accumulation, which negatively impacts health. Its increasing prevalence has led to a global epidemic, emphasizing the urgent need for innovative and effective treatment strategies. This study aims to explore the potential of CRISPR/Cas9-mediated gene editing to enhance UCP1-dependent thermogenesis, offering a novel approach to obesity management. Uncoupling protein 1 (UCP1), primarily located in the inner mitochondrial membrane of brown adipose tissue (BAT), plays a crucial role in thermogenesis and energy expenditure. By converting stored energy into heat, UCP1 activation enhances calorie burning, helping to regulate body temperature and mitigate obesity-related health risks. Recent advancements in genome editing technologies, particularly CRISPR/Cas9, provide a precise method to modify genes involved in UCP1 expression and activity. This approach holds significant promise for sustainable obesity management by enhancing metabolic efficiency and energy expenditure. This study examines the feasibility of using CRISPR/Cas9 to target the UCP1-dependent thermogenesis pathway for obesity treatment. It explores the mechanisms of CRISPR/Cas9, the role of UCP1 in energy regulation, and potential strategies to enhance thermogenic activity. Our findings highlight the promise of CRISPR-based interventions in metabolic regulation. However, further research is necessary to optimize safety, efficacy, and regulatory considerations before translating these findings into clinical applications.